THE INCLUSION OF GAMES AS AN ALTERNATIVE METHOD IN TEACHING MATHEMATICS - Ramos Pereira de Souza, Diego; Alexandre Agreli de Lira Miranda, Ricardo; da Silva Costa, Jucelino; Marcia de Mendonça Oliveira, Girlaine; Aparecida Santos da Silva, Maria; Wilker da Silva, José; de Gouvêa Caldas, Glauco; Maria do Nascimento Domingos, Ramires; Maria Alves, Ivanilda; Bruna da Silva, Maria; de Melo Silva, Inaldevania (Journal of Interdisciplinary Debates, 2025)
This article aims to highlight games in schools as a way of encouraging mathematics teaching, emphasizing the educational aspects that often help students understand mathematical sentences and problems through games. Bibliographic research was conducted with renowned authors who advocate games as a way of including students in schools. It is concluded that mathematical games taught in schools should provide numerous alternatives that lead students not only to abstract concepts and formulas, but also to develop critical and creative thinking, making them capable of making discoveries and understanding the “world” in all its aspects (social, cultural, political, etc.).